Application of Weight Moving Average Method in Forecasting Drug Inventory Application at Dermayu Health Center - Leni Ekasari; Sapri Sapri; Rizka Tri Alinse (Penerbit Jurnal Indonesia, 2021)
The drug inventory forecasting application at Dermayu Public Health Center is an application that is used to predict the amount of drug inventory for the next month based on an analysis conducted on the data on the amount of drug inventory for the last 12 months. In addition, in this application there are 2 (two) methods used for comparative analysis of drug inventory forecasting, namely the Weight Moving Average Method and the Linear Regression Method. Where the comparison of the two methods is seen from the forecasting results and the level of accuracy of the forecast results. With the forecasting results in these 2 (two) methods, it can be used as a reference for the health center in making decisions to manage the amount of drug inventory each month. The drug supply forecasting application was created using the Visual Basic .Net programming language with SQL Server database. Based on the tests that have been carried out, it can be concluded that the functional of the application for forecasting drug supplies at Dermayu Health Center has been running as it should, and the drug inventory forecasting application is able to display the results of forecasting the amount of drug inventory for the next month through 2 methods, namely the Weight Moving Method. Average and Linear Regression Method..